Morpho-physiological growth, yield and fruit quality of rock melon as affected by growing media and electrical conductivity. - Berahim, Zulkarimi; M., Asharfuzaman; Ismail, Mohd Razi (WFL Publisher, 2010)
Effects of soilless media coconut dust (CD) and empty fruit bunch (EFB) and five electric conductivity (EC) levels of fertilizer (0.5, 1.0, 1.5, 2.0 and 2.5 dS/m) on growth, yield and fruit quality of rock melon were investigated under greenhouse conditions. Plant height, number of leaves, total leaf area, chlorophyll content, dry weight of leaf, stem and roots, fruit length, diameter, weight and total soluble solids (sweetness) data were collected. Medium EFB performed better in comparison to CD in all the parameters studied. Among the different EC levels, 1.5 dS/m was most suitable. However, the highest sweetness of the fruit was with EC 2.0 dS/m. The interaction between media and EC levels was significant. Increasing EC level decreased weight of the fruit or fruit yield and increased dry weight of leaf and stem, chlorophyll content and sweetness of the fruit.